ONGs e o Estado: um estudo sobre participação e autonomia - Sucupira, Luciana Abranches (2007)
The public sphere is a space of intersection between the government representation and the society. In consequence, it represents a new dynamic in the society and an increase of the public domain. Because of it’s function, composition, quality and in result it’s relevance, there is a possibility of a participant democracy action. As so, participation and autonomy are bases to construct an increased public sphere. The autonomy is a crucial element to the society, because without it, the participation in the public sphere is incapable of causing transformation. The aim of this work is to understand the relation between the State and Noun Governmental Organizations (NGO), focusing on the organizations leaders, and considering the tension between participation and autonomy. Provided that the NGOs are trying to become more participant in governmental decision. The choice to focus NOGs was based on their importance as politics actors though out Brazilian history, mainly after the 80’s. Also, because though in these institutions the issue of autonomy has been questioned and debated frequently. In order to do so, NGO leaders from Rio de Janeiro, Brasília and São Paulo where interview. It was visible that the autonomy theme is present in all the speeches. Even though examples of limits in the participation, frustrations and embarrassment related with the NGOs actions were part of every interview, there is a coherency in their discourses, related to the conception and at the criterions which give meaning to 'autonomy'. As autonomy is a key element to the NGOs action, is able to realized that it trend is towards the radicalization of democracy, as a result of the deepening of the public sphere.